HUBUNGAN KARAKTER DENGAN MINAT MAHASISWA KEBIDANAN STIKES BINA USADA MENJADI ENTERPRENEUR - I Gede Wirajaya; Alfiery Leda Kio; Nina Rismawati Hakim (NUTRIX, 2020)
Midwifery is one of many professions in the world of health assigned to help the process of labor for mothers, including the caregiving during the childbirth and has as well become the only profession to assist women in the pre and post-labor. The large amount of midwife graduates as counted in every year is contributing in the increasing number of unemployment in Indonesia. For those who had been graduated as a midwife in addition with specific skills of taking care for mothers before and after the birth giving, must have not been unemployed after being equipped with the knowledge of entrepreneurship as there should be an opportunity to create business and new job fields for others. STIKES Bina Usada Bali has inserted entrepreneurship subject to become compulsory in the curriculum to help give new vision to the students. This research is aimed to see the influence of entrepreneurship education to the interest of becoming an entrepreneur for midwifery students of STIKES Bina Usada Bali. The cross sectional design was implemented in this research by applying quantitative method of approach. The data were collected in September 2019 through questionnaire distributed to 39 students of midwifery. The data analysis included Kendall’s Tau univariate and bivariate analysis. The univariate analysis showed that most students had moderate characteristics for entrepreneurship numbered 16 of the total students (43.2%) and those with high interest in entrepreneurship was in the number of 18 students (48.6%). Meanwhile, the bivariate analysis with Kendall Tau’s correlation value of -0.775 showed the presence of weak level of correlation with the value of p=0.00 less than ɑ =0.05 (p<0.05) meaning that there was significant relation between the education of entrepreneurship and the interest in becoming entrepreneurs of the midwifery students of STIKES Bina Usada Bali. Keywords: Entrepreneurship Lectures, Entrepreneurs Interest, Midwifery. Bidan merupakan salah satu profesi dalam dunia kesehatan yang memiliki tugas untuk membantu proses melahirkan pada seorang ibu, memberi asuhan pada masa persalinan dan menjadi satu–satunya profesi yang memiliki tugas untuk merawat seorang wanita yang akan melahirkan dan juga setelah melahirkan. Banyaknya lulusan bidan setiap tahunnya menjadi salah satu penyebab meningkatnya jumlah pengangguran di Indonesia. Lulusan bidan yang sudah memiliki kemampuan yang khusus dalam bidang pengasuhan dan perawatan seorang ibu yang sedang mengandung dan setelah melahirkan, seharusnya tidak menjadi pengangguran ketika mereka dibekali pengetahuan tentang entrepreneurship, karena mereka dapat membangun usaha mereka sendiri dan bahkan mampu membuka lapangan pekerjaan. STIKES Bina Usada Bali menambahkan mata kuliah entrepreneurship sebagai salah satu mata kuliah yang wajib diambil oleh mahasiswa untuk memberikan pandangan baru kepada mahasiswa. Penelitian ini bertujuan untuk melihat pengaruh pendidikan entrepreneurship terhadap minat mahasiswa kebidanan STIKES Bina Usada Bali menjadi seorang entrepreneur. Rancangan penelitian ini adalah cross sectional menggunakan pendekatan kuantitatif. Pengumpulan data dilakukan pada bulan September 2019 melalui pengisian kuesioner oleh 39 mahasiswa kebidanan. Analisis data meliputi analisis univariat dan bivariat Korelasi Kendall’s Tau. Analisis univariat menunjukkan bahwa sebagian besar memiliki karakter entrepreneur sedang sebanyak 16 mahasiswa (43,2%) dan mahasiswa yang memiliki minat tinggi menjadi entrepreneur sebanyak 18 mahasiswa (48,6%%). Analisis bivariat dengan nilai korelasi Kendall’s Tau sebesar -0,775 menunjukkan adanya tingkat hubungan yang lemah dengan nilai p= 0,00 lebih kecil dari α = 0,05 (p<0,05) yang berarti ada hubungan yang signifikan antara pendidikan entrepreneurship dengan minat mahasiswa kebidanan STIKES Bina Usada Bali menjadi entrepreneur. Kata Kunci: Kuliah Entrepreneurship, Minat Entrepreneur, Bidan.